2020
DOI: 10.1002/jcla.23217
|View full text |Cite
|
Sign up to set email alerts
|

IgA is the predominant isotype of anti‐β2 glycoprotein I antibodies in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, inflammatory joint disease of autoimmune nature. The ethiopathogenic mechanisms involved are complex and include gut dysbiosis. 1 RA is characterized by autoantibodies production (rheumatoid factor (RF) and anti-citrullinated protein antibody (ACPA)). RA can lead to accumulating joint damage and irreversible disability. 2 Antiphospholipid antibodies (aPL) are a heterogeneous group of antibodies that have been associated with thrombotic or obstetrical events in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…However, aβ2GPI‐IgA can be observed in autoimmune diseases other than APS. In fact, we have previously demonstrated a significantly higher frequency of aβ2GPI‐IgA in patients with celiac disease, primary biliary cholangitis, and RA than in a healthy population 7–9 …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, aβ2GPI‐IgA can be observed in autoimmune diseases other than APS. In fact, we have previously demonstrated a significantly higher frequency of aβ2GPI‐IgA in patients with celiac disease, primary biliary cholangitis, and RA than in a healthy population 7–9 …”
Section: Discussionmentioning
confidence: 95%
“…In fact, we have previously demonstrated a significantly higher frequency of aβ2GPI-IgA in patients with celiac disease, primary biliary cholangitis, and RA than in a healthy population. [7][8][9] In this study, the frequency of antibodies of RA (CCP-Ab or RF)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding could be explained by the effect of tobacco smoking on tissue protein citrullination, and also detonate of autoantibodies synthesis, which show to induce the disease progression and disease activity in patients with rheumatoid arthritis. [42][43][44] On the other hand, the association of DAS-28 and VLDL-C levels is not clear yet, but it has been reported that RA patients with high disease activity had alterations of the lipid profile. 38,45 Rheumatoid factor (RF) correlated with age and smoking index, which agrees with other reports [46][47][48] ; likewise, RF correlated with triglycerides, which could be explained by this autoantibody´s positive correlation with a high RA disease activity, 49 a status associated with lipids alteration.…”
Section: Discussionmentioning
confidence: 99%